Assessment of a new score for capsule endoscopy in pediatric Crohnʼs disease (CE-CD) - Oliva, Salvatore; Veraldi, Silvio; Cucchiara, Salvatore; Russo, Giusy; Spagnoli, Alessandra; Cohen, Stanley Allen (Endoscopy International Open, 2021)
Background and study aims Two scores have been implemented to standardize capsule endoscopic (CE) findings in patients with Crohn’s disease (CD): Lewis score (LS) and Capsule Endoscopy Crohnʼs Disease Activity Index (CECDAI). Both have limitations and are not well validated in the pediatric population. The aim of our study was to assess a new score (capsule endoscopy – Crohn’s disease index, CE-CD) in pediatric patients with CD and to compare it to preexisting scores.Patients and methods This was a double-center, retrospective study involving pediatric subjects with CD who underwent CE. Correlation analyses between CE-CD, endoscopy scores and noninvasive markers of disease activities were performed. The ability of different CE scores to predict clinical and endoscopic outcomes was evaluated with regression and survival analyses.Results A total of 312 subjects were analyzed. The CE-CD score showed a moderate (Pearson’s r = 0.581, P < 0.001) and strong (r = 0.909, P < 0.001) association with LS and CECDAI, respectively. CE-CD was a statistically significant predictor of hospitalization (hazard ratio [HR]1.061), treatment escalation (HR 1.062), steroid therapy (HR 1.082), clinical (HR 1.064) and endoscopic (HR 1.060) relapse over the twenty-four months (P < 0.001). Subjects with mucosal inflammation according to CE-CD (CE-CD ≥ 9) had worse outcomes compared to patients without inflammation (CE-CD < 9) (Log rang test < 0.001).Conclusions The CE-CD score is a simple, reliable, reproducible, and predictive score for evaluation of small bowel inflammation in pediatric patients with CD. Prospective validation is needed to confirm the applicability of this new index in clinical practice.